2009
DOI: 10.1074/jbc.m109.033472
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil MMP-9 Proenzyme, Unencumbered by TIMP-1, Undergoes Efficient Activation in Vivo and Catalytically Induces Angiogenesis via a Basic Fibroblast Growth Factor (FGF-2)/FGFR-2 Pathway

Abstract: The structural and catalytic requirements for neutrophil MMP-9 proenzyme (proMMP-9) to induce angiogenesis were investigated using a quantitative angiogenesis model based on grafting of collagen onplants onto the chorioallantoic membrane of chick embryos. Both physiological activation of neutrophil proMMP-9 and proteolytic activity of the generated MMP-9 enzyme were critically dependent on the tissue inhibitor of metalloproteinase (TIMP)-free status of the zymogen. The presence of an intact active site and hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 62 publications
4
125
1
1
Order By: Relevance
“…2,19,21,35 A recent study demonstrated that tissueinfiltrating neutrophil pro-MMP-9 induces angiogenesis catalytically via an FGF-2/FGFR2 pathway. 23 Consistent with that study, we have shown previously that pharmacologic PAI-1 inhibition results in the accumulation of FGF-2-and VEGF-A-expressing Gr-1 ϩ neutrophils within ischemic muscle tissues through an effect on endogenous tPA and MMP-9, and in an increase of plasma VEGF-A via up-regulation of endogenous tPA. 19 Neutrophils can secrete tissue inhibitors of metalloproteinase (TIMP)-free MMP-9 that can act in concert with, for example, macrophages to liberate proangiogenic growth factors such as VEGF and FGF-2 that are sequestered to the extracellular matrix.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…2,19,21,35 A recent study demonstrated that tissueinfiltrating neutrophil pro-MMP-9 induces angiogenesis catalytically via an FGF-2/FGFR2 pathway. 23 Consistent with that study, we have shown previously that pharmacologic PAI-1 inhibition results in the accumulation of FGF-2-and VEGF-A-expressing Gr-1 ϩ neutrophils within ischemic muscle tissues through an effect on endogenous tPA and MMP-9, and in an increase of plasma VEGF-A via up-regulation of endogenous tPA. 19 Neutrophils can secrete tissue inhibitors of metalloproteinase (TIMP)-free MMP-9 that can act in concert with, for example, macrophages to liberate proangiogenic growth factors such as VEGF and FGF-2 that are sequestered to the extracellular matrix.…”
Section: Discussionsupporting
confidence: 68%
“…FGF-2 signaling has been associated with neutrophil-mediated angiogenesis 23 and PAI-1 activity. 22 Immunohistochemical analysis of ischemic muscle tissues demonstrated that the number of F4/80 ϩ cells coexpressing FGF-2 or VEGF-A was not significantly different from vehicle-and PAI-1 inhibitor-treated tissues ( Figure 6B).…”
Section: The Proangiogenic Pai-1 Inhibitor Enhances Fgf-2 and Vegf-a mentioning
confidence: 99%
“…After the Jak-2-STAT3 pathway is activated, the expression of downstream target genes may be up-regulated or down-regulated. These genes are related to tumor angiogenesis including Vegf, Hif-1a, bFgf, Mmp-2, Mmp-7, Mmp-9, and so on (Xie et al 2004, Jung et al 2007, Ardi et al 2009, Behera et al 2010, Ferrara 2010. It can be inferred that the activation of Jak-2-STAT3 can promote tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…117 Furthermore, thrombin-mediated invasion of U2 osteosarcoma cells involved a PEX9 and β 1 -integrin association, 118 while MMP9 catalytic and PEX domains have been reported to induce FGF2-mediated angiogenesis in neutrophils. 119 With respect to other MMPs, Suenaga et al 120 reported that binding of CD44 to the MMP14 PEX domain is critical for shedding of human fibrosarcoma and breast carcinoma cells. In addition, Eisenach et al described an MMP14-VEGFR2-Src complex formation that controls VEGFR2 cell-surface localization through hemopexin-dependent activity in breast cancer cells.…”
Section: Mmps As Signaling Molecules Noncatalytic Functionsmentioning
confidence: 99%